2020
DOI: 10.3390/jcm9020495
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Periodontitis and Periodontal Bacteria in the Onset and Progression of Alzheimer’s Disease: A Systematic Review

Abstract: The evidence of a connection between the peripheral inflammatory processes and neurodegenerative diseases of the central nervous system is becoming more apparent. This review of the related literature highlights the most recent clinical, epidemiological, and in vitro studies trying to investigate possible connections between periodontal bacteria and the onset and progression of Alzheimer’s disease. This review was conducted by searching databases such as PubMed and Scopus using keywords or combinations such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 88 publications
(96 reference statements)
1
85
0
5
Order By: Relevance
“…Worldwide, it affects up to 60% of the population [8,9]. There appears to be an association of periodontitis with certain systemic diseases such as cardiovascular disease, complications in pregnancy or Alzheimer's disease [10,11]. The pathogenesis of periodontal diseases is mediated by the inflammatory response of the host to the bacteria in the subgingival plaque [12].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, it affects up to 60% of the population [8,9]. There appears to be an association of periodontitis with certain systemic diseases such as cardiovascular disease, complications in pregnancy or Alzheimer's disease [10,11]. The pathogenesis of periodontal diseases is mediated by the inflammatory response of the host to the bacteria in the subgingival plaque [12].…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between periodontitis and systemic inflammation is well documented [42,43]. A recent systematic review confirmed that periodontal bacterial load and gum inflammatory burden can intensify the neuroinflammation in the central nervous system in Alzheimer's disease (AD), favoring the onset and progression of this neurodegenerative condition [44]. Accumulating evidence has shed light on how neuroinflammation can play a key role on the PD pathogenesis and neurodegeneration [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The following review was performed on the basis of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) [25] indications. The methodology has already been adopted in other systematic reviews on the topic (Actinomyces and Propionibacterium) by the same authors [26][27][28].…”
Section: Methodsmentioning
confidence: 99%